Group Activity Therapy (TAK) diabetes foot exercises for the elderly at Posbindu Seruni, Depok City - Nourmayansa Vidya Anggraini; Teguh Firmansyah (Community Empowerment, 2024)
Old age is a life stage marked by changes that lead to a decline in bodily functions. One therapeutic approach employed for the elderly is group activity therapy, specifically focusing on foot exercises. The objective of this activity is to reduce morbidity among elderly individuals with diabetes mellitus. Engaging in foot exercises enhances blood circulation in elderly individuals suffering from diabetes mellitus, leading to increased strength in their leg muscles. The group activity therapy for elderly individuals with diabetes mellitus took place at Posbindu Seruni, attracting 19 participants. The activity involved group therapy sessions incorporating diabetic foot exercises. Based on the evaluation results, there was an increase in knowledge among TAK participants by 12.63%. Thus, health education and group activity therapy can be developed as sustainable health promotion initiatives. This approach aims to optimize the knowledge level of the elderly, facilitate a positive shift in their health behavior from maladaptive to adaptive, and help prevent the severity of diabetes mellitus through regular participation in diabetes foot exercises.